Electrophysiological and morphological properties of rat basolateral amygdaloid neurons in vitro - Washburn, MS (J Neurosci, 1992)
Electrophysiological and morphological properties of neurons in the rat basolateral amygdala (BLA) were assessed using intracellular recordings in brain slice preparations. The vast majority of cells studied were identified as pyramidal cells on the basis of their accommodation response and by a prominent afterhyperpolarization that followed a current-evoked burst of action potentials. The second class of cells consisted of late-firing neurons that were distinguished electrophysiologically by their very negative resting membrane potential (-82 mV) and conspicuous delay in the onset of spike firing in response to depolarizing current injection. The third class of cells, termed fast-firing neurons, possessed many of the features of intrinsic inhibitory interneurons found elsewhere in the brain. These included very brief action potentials (0.7 msec), a relatively depolarized resting membrane potential (-62 mV), and spontaneous firing at a high rate and the absence of spike frequency accommodation. Intracellular labeling with Lucifer yellow of electrophysiologically identified pyramidal and late-firing cells showed them to have pyramidal to stellate cells bodies and spine-covered dendrites. Although having an overall pyramidal-like morphology, late-firing neurons possessed cells bodies and dendritic fields that were smaller than those of pyramidal cells. Lucifer yellow-labeled fast-firing neurons had a nonpyramidal morphology, with somata that were spherical to multipolar in shape and spine-sparse or aspiny dendrites. The morphological features of these cells corresponded closely to those of GABA-containing interneurons that have been described previously in the rat BLA using immunohistochemical techniques (McDonald, 1985b). Thus, it seems likely that activation of fast-firing neurons underlies inhibitory synaptic events that are recorded in the rat BLA. Our data support the conclusion derived from previous anatomical studies that pyramidal neurons constitute the predominant cell type in the BLA and function as projection neurons in this region of the amygdala. The determination of whether late-firing cells constitute a unique class of projection neurons distinct from pyramidal cells must await the outcome of studies in which the anatomical terminations of this cell type are specified.